2005
DOI: 10.1002/ijc.20680
|View full text |Cite
|
Sign up to set email alerts
|

Radon and other natural radionuclides in drinking water and risk of stomach cancer: A case-cohort study in Finland

Abstract: Very high concentrations of naturally occurring radionuclides are encountered in Finnish groundwaters and wells. Radon ingested through drinking water can cause considerable radiation to the stomach. We assessed the effect of natural uranium and other radionuclides in drinking water on the risk of stomach cancer. Subjects (n ‫؍‬ 144,627) in the base cohort had lived outside the municipal tap water system during 1967-1980. A subcohort of 4,590 subjects was formed for use as a reference group by random sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 11 publications
1
51
3
3
Order By: Relevance
“…Cancer risk also increased with the consumption of fresh water fish in the study area (Phatcha et al, 2006). Similar case control study identified significant correlation between other type of cancer and ingested radionuclides (Auvinen et al, 2002;. Contrariwise, ecological studies in Harris country associated birth defects to ingestion of high radium in water (Cech et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…Cancer risk also increased with the consumption of fresh water fish in the study area (Phatcha et al, 2006). Similar case control study identified significant correlation between other type of cancer and ingested radionuclides (Auvinen et al, 2002;. Contrariwise, ecological studies in Harris country associated birth defects to ingestion of high radium in water (Cech et al, 2008).…”
Section: Introductionmentioning
confidence: 80%
“…Una de las principales funciones de la salud pública es la identificación de estos peligros para tratarlos y minimizar su efecto evitando daños sobre las personas. Los estudios epidemiológicos confirman que el radón aumenta el riesgo de cáncer de pulmón, (12), existen estudios realizados sobre mineros que demuestran una causa efecto derivada de su exposición (13) otros estudios sugieren incluso su relación con otro tipo de cánceres como el de estómago al ingerir agua con gas radón disuelto (14). La proporción de caso de cáncer de pulmón asociados al radón en relación al total varía entre un 3 a un 14% dependiendo de la concentración media de radón en el país, en muchos países el radón es la segunda causa de cáncer de pulmón detrás del tabaco siendo un factor sumatorio en aquellas personas que están expuestas al gas y tienen hábitos tabáquicos.…”
Section: El Radón: Un Problema Para La Salud Públicaunclassified
“…The South-West of England has both the most noteworthy rates of non-melanoma skin cancer (NMSC) and the most noteworthy average radon concentrations in the UK, with epidemiological proof now proposing that in Devon and Cornwall expanded household private radon presentation might be a hazard consider for the improvement of squamous cell carcinoma of the skin [23]. It ought to be noticed that various different cancers have additionally been recommended to have an expanded hazard with high radon concentrations including leukemia and gastrointestinal malignancies, albeit any confirmation of a cause-impact relationship stays theoretical [24,25].…”
Section: The Cellular and Molecular Carcinogenic Effects Of Radon Expmentioning
confidence: 99%